Anticancer activity of alangium salvifolium flower in ehrlich ascites carcinoma bearing mice - Zahan, Ronok; Alam, Md. Badrul; Islam, Saiful; S. Chowdhury, Nargis; B. Hosain, Salman; Mosaddik, Ashik; Jesmin, Mele; Haq, M. Ekramul (© 2011 Academic Journals Inc., 2016)
This article was published in International Journal of Cancer Research [© 2011 Academic Journals Inc.] and the definite version is available at : http://scialert.net/qredirect.php?doi=ijcr.2011.254.262&linkid=pdf